DNA Damage: A Sensible Mediator of the Differentiation Decision in Hematopoietic Stem Cells and in Leukemia - Weiss, Cary N. (Int J Mol Sci, 2015)
In the adult, the source of functionally diverse, mature blood cells are hematopoietic stem cells, a rare population of quiescent cells that reside in the bone marrow niche. Like stem cells in other tissues, hematopoietic stem cells are defined by their ability to self-renew, in order to maintain the stem cell population for the lifetime of the organism, and to differentiate, in order to give rise to the multiple lineages of the hematopoietic system. In recent years, increasing evidence has suggested a role for the accumulation of reactive oxygen species and DNA damage in the decision for hematopoietic stem cells to exit quiescence and to differentiate. In this review, we will examine recent work supporting the idea that detection of cell stressors, such as oxidative and genetic damage, is an important mediator of cell fate decisions in hematopoietic stem cells. We will explore the benefits of such a system in avoiding the development and progression of malignancies, and in avoiding tissue exhaustion and failure. Additionally, we will discuss new work that examines the accumulation of DNA damage and replication stress in aging hematopoietic stem cells and causes us to rethink ideas of genoprotection in the bone marrow niche.